Institutional Factor in International Economic Activity of Region and Its Socio-Economic Development - Andreeva, Elena Leonidovna; Linetsky, Aleksandr Fyodorovich; Ratner, Artem Vitalyevich; Kuznetsova, Darya Evgenyevna (Economy of Regions, 2016)
The article substantiates the impact of the institutional factor on the development of regional international economic relations. The scope of the study is regional international economic activity (IEA), the subject-matter is the role of the institutional factor in its development. The study purpose is to develop a scientific approach for the assessment of the institutional factor impact on the development of region's international economic relations. The hypothesis is that the targeted efforts of all participants of IEA of the region (business, authorities, local community) to strengthen of theese components of the institutional factor, which have a strong influence on the regional socio-economic development. A methodological approach for the assessment of this influenceis developed. It includes determining three elements of IEA institutionalization -agreements, organizations, events. A three-dimensional model is proposed for the coordination of these elements with 3 groups of countries-developed, developing and CIS, including the Eurasian Economic Union, and also with basic indexes characterizing the qualitative and quantitative contribution of region's IEA into its socio-economic development. This model is tested on the example of the Sverdlovsk region of Russia for 2003-2015. That has allowed to define various kinds of the effects from strenthening the IEA institutional component, which are expressed in the increase of the export of the region, improvement of its investment attractiveness, the diversification of regional economy as well as the the generation of additional jobs and tax flows increase.